(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2024)
This study aims to explain the relationship between politics and technology by specifically discussing how the Internet supports and hinders democracy. This conceptual elaboration was prompted by recent controversies about the democratic power of the Internet. The controversy is framed in three perspectives, namely the perspective of utopia, dystopia, and syntopia. By using a qualitative approach and constructivist paradigm as well as literature studies, this paper argues that the three perspectives are reductionist and simplistic. Based on their technological determinism approach, they ignore subject agency and socio-cultural context in framing the relationship between the Internet and democracy. This paper offers holistic reading that the success and failure of technology adoption in democratic practice is a product of the organic interaction between technology and subject agency as well as social, political, and cultural contexts.